Early experiences of rehabilitation for individuals post-COVID to improve fatigue, breathlessness exercise capacity and cognition – A cohort study. (5th May 2021) - Daynes, Enya; Gerlis, Charlotte; Chaplin, Emma; Gardiner, Nikki; Singh, Sally J
Individuals with lasting symptoms of COVID-19 should be offered a comprehensive recovery programme. 30 individuals (mean[SD] age 58[16]) that completed a 6 week, twice supervised rehabilitation programme demonstrated statistically significant improvements in exercise capacity, respiratory symptoms, fatigue and cognition. Participants improved by 112 m on the Incremental Shuttle Walking Test and 544 seconds on the Endurance Shuttle Walking Test. There were no serious adverse events recorded, and there were no dropouts related to symptom worsening. COVID-19 rehabilitation appears feasible and significantly improves clinical outcomes.